Examining how the geographic availability of alcohol within residential neighborhoods, activity spaces, and destination nodes is related to alcohol use by parents of young children. (1st April 2022) - Freisthler, Bridget; Wernekinck, Uwe
Abstract: Background: Alcohol outlet density and drinking behaviors have been assessed based on where people live, but exposure may differ based on where people spend time. We assessed the relationship between alcohol outlet density (using three measures of geographic availability), frequency of use, and continued volume of alcohol among parents. Parents are a unique population of drinkers where the risk for harm to others can be higher as they are caring for minor children. Methods: We conducted a cross-sectional telephone and web-based survey of 1599 parents in 2015 across 30 cities in California. Participants provided information on drinking, residential addresses, and locations of daily activities. We created three measures of alcohol availability using residential neighborhoods, convex hull polygons, and destination nodes. Data were analyzed using zero-inflated negative binomial models. Results: Density of bars in residential neighborhoods were related to more frequent drinking ( b = 0.0139, 95% CI = 0.0016, 0.0261) and higher continued volume ( b = 0.0295, 95% CI = 0.0067, 0.0522). Density of bars ( b = 0.0070, 95% CI = 0.0019, 0.0121) and restaurants ( b = 0.0018, 95% CI = 0.0003, 0.0033) in destination nodes were related to drinking a higher continued volume of alcohol. Higher off-premise outlet density was related to a lower continued volume ( b = −0.0026, 95% CI = −0.0049, −0.0002). Conclusions: Outlet densities in residential neighborhood and destination nodes are related to frequency of drinking and continued volume of alcohol. Future work should seek to determine why and how residential neighborhoods and nodes are related to alcohol use behaviors and if they differ for parents compared to other adults. Highlights: Parents living in neighborhoods with lots of bars drink more often and higher volumes. Parents with activities in areas with more on-premise outlets drink higher volumes. Parents with activities in areas with more off-premise outlets drink lower volumes.